Up-conversion luminescent properties and optical thermometry of LaMgAl11O19: Yb3+/Er3+ phosphors. Issue 10 (December 2015) - Fu, Linlin; Liu, Guofeng; Yang, Xingxing; Fu, Zuoling; Yang, Yanmin
Abstract: LaMgAl11 O19 : Yb 3+ /Er 3+ phosphors were successfully synthesized by a conventional sol–gel method with a lower temperature. The composition and phase purity of the samples were examined by X-ray diffraction (XRD). Under 980 nm excitation, the phosphors exhibited efficient visible up-conversion (UC) emissions including strong green emission centered at 525, 545 nm, and weak red emission centered at around 657 nm, which were assigned to the 2 H11/2 → 4 I15/2, 4 S3/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 transitions of Er 3+ ions, respectively. The process involved in the UC emission was evaluated in detail by energy level diagram and the pump power dependence. To investigate the sensing application of the synthesized phosphor materials, temperature-sensing performance was studied in the temperature range of 298–573 K using the fluorescence intensity ratio technique. The maximum sensitivity was found to be approximately 0.00267 K −1, indicating its applicability as an optical temperature sensor.